Vascular endothelial growth factor (VEGF) polymorphism rs3025039 and atherosclerosis among older with hypertension - Shimizu, Yuji; Arima, Kazuhiko; Noguchi, Yuko; Yamanashi, Hirotomo; Kawashiri, Shin-Ya; Nobusue, Kenichi; Nonaka, Fumiaki; Aoyagi, Kiyoshi; Nagata, Yasuhiro; Maeda, Takahiro (Scientific reports, 2022)
Angiogenesis inhibition therapy causes hypertension by increasing peripheral vascular resistance. Vasa vasorum angiogenesis plays a crucial role in the development of atherosclerosis. Since vascular endothelial growth factor (VEGF), which contributes to the progress of angiogenesis, is reported to be inversely associated with the minor allele of polymorphism rs3025039, the minor allele of rs3025039 could be inversely associated with atherosclerosis among individuals with hypertension. A cross-sectional study of 1793 older Japanese adults aged 60–89 years with hypertension who participated in general health check-ups was conducted. Atherosclerosis was defined as carotid intima-media thickness (CIMT) ≥ 1.1 mm. The minor allele of polymorphism rs3025020 was positively associated with VEGF. Therefore, in addition to known cardiovascular risk factors, rs3025020 genotype acted as a confounding factor in the present study. Independent of known confounding factors, the minor allele of rs3025039 was inversely associated with atherosclerosis among older Japanese adults with hypertension. The fully adjusted odds ratio (OR) and 95% confidence interval (CI) for atherosclerosis with the minor allele of rs3025039 was 0.78 (0.64, 0.96). The angiogenesis-related polymorphism rs3025039 was associated with the development of atherosclerosis among older Japanese individuals. This study indicates that the development of atherosclerosis among older individuals might partly indicate a capacity for angiogenesis.